Examining the Value Chain in Achieving Educational Multicultural-based Innovation: A Cost Leadership Perspective - Samsul Ma’arif (Dinamika Ilmu, 2023)
The existing management of Madrasah Ibtidaiyyah’s education has not been able to play a role in preparing the expected graduates. This situation occurred because Madrasah Ibtidaiyyah (MI) did not know what innovations would produce professional graduates who could become role models from the ubudiyah side and tolerant of differences. This research aims to explore madrasah education activities in developing local and national content from a value chain perspective in achieving educational innovation based on multicultural. This research used qualitative methods, with a case study approach. This research takes MI Al Ahmad Krian, Sidoarjo as an object. Value chain activities implemented in the school provided extra value in developing local and national content. The cost leadership implemented by the school succeeded in creating 1) quality-based educational services at affordable cost, 2) community satisfaction of the motto “School based on the Qur’an, global and environment,” and 3) parent’s pride in their children with advanced academic achievements, practices of ubudiyah, and reciting Qur’an.